2018
DOI: 10.1017/s0017089518000484
|View full text |Cite
|
Sign up to set email alerts
|

Free Actions of Some Compact Groups on Milnor Manifolds

Abstract: In this paper, we investigate free actions of some compact groups on cohomology real and complex Milnor manifolds. More precisely, we compute the mod 2 cohomology algebra of the orbit space of an arbitrary free ℤ2 and $\mathbb{S}^1$-action on a compact Hausdorff space with mod 2 cohomology algebra of a real or a complex Milnor manifold. As applications, we deduce some Borsuk–Ulam type results for equivariant maps between spheres and these spaces. For the complex case, we obtain a lower bound on the Schwarz gen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…We list here some results from [7] related to free actions of Z 2 and S 1 on Milnor manifolds that we are going to use to compute lower bounds on the (equivariant) LS-category and topological complexity of Milnor manifolds. Then F H r,s admits a free involution if and only if both r and s are odd integers, where F is either R or C .…”
Section: Theorem 210 ([19]mentioning
confidence: 99%
See 1 more Smart Citation
“…We list here some results from [7] related to free actions of Z 2 and S 1 on Milnor manifolds that we are going to use to compute lower bounds on the (equivariant) LS-category and topological complexity of Milnor manifolds. Then F H r,s admits a free involution if and only if both r and s are odd integers, where F is either R or C .…”
Section: Theorem 210 ([19]mentioning
confidence: 99%
“…Milnor [18, Lemma 1] shown that the unoriented cobordism algebra of smooth manifolds is generated by the cobordism classes of real projective spaces and real Milnor manifolds. P. Dey and M. Singh [7] characterized milnor manifolds which admits free Z 2 and S 1 -actions with restriction on r and computed the equivarinat cohomology rings in this case. The purpose of this paper is to compute the LS-category and topological complexity of Milnor manifolds.…”
mentioning
confidence: 99%
“…□ In order to investigate the existence of free involutions on a Milnor manifold X ¼ Hm , n ðÞ , Dey and Singh [34] showed that if G ¼  2 acts freely on X, with 1 < n < m and m À 2 mod4 ðÞ , then necessarily m and n must be odd. Furthermore, they construct some examples of such free actions and, in this case, it follows that…”
Section: Free Actions On Dold Wall and Milnor Manifoldsmentioning
confidence: 99%
“…There are interesting problems related to transformation groups, for example, to classify the fixed point set X G , the existence of free/semifree actions and the study of the orbit space X/G for free actions of G on X. A number of results has been proved in the literature in this direction [1,3,5,6,10,11]. An another thread of research is to classify X for a given orbit space X/G when G acts freely on X. Su [12] proved that if G = S d , d = 0, 1, acts freely on a space X and the orbit space X/G is cohomology FP n , then space X is the cohomology sphere S (d+1)n+d , when d = 0, F = R with Z 2 coefficients, and when d = 1, F = C with integer coefficients.…”
Section: Introductionmentioning
confidence: 99%